Benthic foraminifera as palaeo-environmental indicators in the Northern Gulf of Cadiz - Mendes, Isabel Maria de Paiva Pinto (2010)
This thesis is an investigation of benthic foraminifera as palaeo-environmental indicators on the Northern Gulf of Cadiz continental shelf, northeast Atlantic Ocean. The main objective was to determine the environmental indicator value of living benthic foraminifera and their application to Holocene palaeoenvironmental reconstruction. Relationships between living benthic foraminiferal fauna and both physical and chemical parameters were analysed in surficial samples collected from the continental shelf between the Guadiana and Guadalquivir Rivers. Living benthic foraminiferal faunas were characterised in detail and associations of the most abundant species classified into four groups. These groups allowed the characterisation of the modern environment and associated physical and chemical parameters. Sedimentological and benthic foraminiferal analyses, combined with a chronological framework, were performed on three Holocene sequences from contrasting sedimentary environments. A comparison between the most abundant species in living faunas and those occurring in Holocene shelf sediments was also made. An integrated approach using all the available information sheds light on paleoenvironmental changes, which were distilled into five evolutionary scenarios. Each scenario is a representation of the environmental changes that characterised the three studied environments at different times during the Holocene. They indicate the influence of various factors, including sea-level changes, river discharge and substrate properties, that are mirrored by different benthic foraminiferal assemblages. The thesis demonstrates that the modern ecological preferences of common benthic foraminiferal species have direct applicability to interpreting the palaeoenvironmental record.